Jewish City or Inferno of Russian Israel? A History of the Jews in Kiev Before February 1917. - Victoria Khiterer (Academic Studies Press, 2016)
This book describes the history of Jews in Kiev from the tenth century to the February 1917 Revolution. At the turn of the twentieth century, the Kiev Jewish community was one of the largest and wealthiest in the Russian Empire. This book illuminates the major processes and events in Kievan Jewish history, including the creation of the Jewish community, the expulsions of Jews from the city, government persecution and Jewish pogroms, the Beilis Affair, the participation of Jews in the political, economic, and cultural life of Kiev, and their contribution to the development of the city.
Introduction -- Chapter one. The history of Jews in Kiev from the tenth century to 1660 -- Chapter two. The Jews of Kiev in the embrace of the Russian empire (1794-1859) -- Chapter three. The Jewish right of residence in Kiev in 1859-1917 -- Chapter four. The Kiev Jewish community and its leaders -- Chapter five. The wealth and poverty of Jews in Kiev -- Chapter six. Jewish pogroms and the Beilis Affair -- Chapter seven. How Jews gained their education in Kiev -- Chapter eight. Jewish culture in Kiev -- Chapter nine. Between tradition and modernity: Jewish religious life in Kiev -- Conclusion.
Print version record.
Includes bibliographical references (pages 437-457) and index.
Master record variable field(s) change: 650
Keywords: Jews -- Ukraine -- Kyïv -- History; HISTORY -- Europe -- Eastern; HISTORY -- Europe -- Former Soviet Republics; HISTORY -- Europe -- Russia & the Former Soviet Union; Jews; Ukraine -- Kiev; History; Electronic books